Pulmonary wedge injections yielding left-sided echocardiographic contrast. Issue 4 (October 1980) - Meltzer, R S; Serruys, P W; McGhie, J; Verbaan, N; Roelandt, J
Abstract : Ultrasound contrast on the left side of the heart without the need for left heart catheterisation was achieved by hand injections of 8 to 10 ml 5 per cent dextrose solution through a catheter in the pulmonary wedge position. Injections were performed in 18 patients undergoing routine cardiac catheterisation and M-mode or two-dimensional echocardiography was used. An adequate wedge position was attained in 17 of the 18 patients. Nine had injections through Cournand catheters, three through Swan-Ganz catheters, and five through both. In 11 of these 17 patients left atrial or left ventricular echocardiographic contrast was seen immediately after wedge injection. Two patients showed diminished or absent contrast on later injections from the same position. Better results were obtained with the Cournand catheter (11/15 positive) than with the Swan-Ganz (1/8 positive) catheter. Pulmonary artery injections proximal to the wedge position did not cause left-sided contrast. No complications were observed. The safety of this method remains to be determined.